The Cave-Dwelling Ground Beetles on the Azores (Col.: Carabidae) - Borges, Paulo A. V. (1991)
In the present paper, the taxonomy of endemic species of "Thalassophillus" and "Trechus" from the Azores is studied, and the ecology, biogeography and possible evolution of these beetles are briefly discussed.